Forward and backward aortic components and reflection indexes in children and adolescents: Determinants and role in high pressure states - Zocalo, Yanina (2018)
Background: High blood pressure states (HBP) would differ in wave components and reflections indexes, which could associate clinical and prognostic implications. The study aims: 1) to characterize the association of aortic wave components and reflection parameters (backward [Pb], forward [Pf], Pb/Pf ratio and augmentation index [AIx]) with demographic, anthropometric, hemodynamic and arterial parameters in healthy children and adolescents; 2) to generate multivariate prediction models for the associations, to contribute to understand the main determinants of Pf, Pb, Pb/Pf and AIx; 3) to identify if differences in wave reflection indexes observed in HBP could be explained by differences in the analyzed parameters. Methods: Healthy children and adolescents (n=816, females: 386; Age: 3-20 years) were studied. Evaluations: central aortic pressure and wave components (Pb, Pf, Pb/Pf and AIx determination with SphygmoCor [SCOR] and Mobil-o-Graph [MOG]); anthropometric assessment; regional arterial stiffness (carotid-femoral, carotid-radial pulse wave velocity [PWV] and PWV ratio); carotid intima-media thickness; carotid and femoral distensbility; cardiac output; systemic vascular resistances (SVR). Simple and multiple regression models were constructed to determine aortic wave parameters; the main explanatory variables. Normotensive and HBP groups were compared. Differences in wave reflection indexes were analyzed before and after controlling for explanatory variables. Equivalences between SphygmoCor and Mobil-O-Graph data were assessed (correlation and Bland-Altman analyses). Results and Conclusion: There were systematic and proportional differences between the data obtained with SphygmoCor and Mobil-O-Graph devices. Heart rate (HR), peripheral pulse pressure, height and weight were the variables that isolated (simple associations) or combined (multiple asso-ciations), showed the major capability to explain interindividual differences in Pf, Pb, Pb/Pf and AIx. Arterial stiffness also showed explanatory capacity, being the carotid the artery with the major contribution. HBP associated higher Pf, Pb, AIx and lower Pb/Pf ratio. Those findings were observed together with higher weight, arterial stiffness and HR. After adjusting for anthropometric characteristics, HR, cardiac output and SVR, the HBP group showed greater Pf and Pb. Then, Pf and Pb characteristics associated with HBP would not be explained by anthropometric or hemodynamic factors. Evaluating wave components and reflection parameters could contribute to improve the comprehension and management of HBP states.